Shoot Cutting Jarak Pagar pada Tingkatan Umur Ontogeni dan Zat Pengatur Pertumbuhan - Zasari, Maera (ENVIAGRO, 2010)
Shoot cutting Jarak Pagar research is purposed to understand the influential of bud ontogeny age and concentration of plant growth regulators (PGRs) to the growth of the cutting. This research is carried out at experimental garden of Agriculture, Fisheries and Biology Faculty of UBB at Sungailiat, Bangka. The research is held from March to November 2008. The Experiment used Randomize Complete Block Design (RCBD) that consist of ontogeny age of the cutting and concentration of PGRs.Â  The result of the research shows that juvenile age of the jarak pagar cutting give better result to all observed variables, except length of roots dan growth of ability. Plant Growth Regulators (IBA or NAA) generally gives better influence at consentration less than 6.000 ppm, except length of roots, fresh weigth and dry weigth of roots at 4000 to 6000 ppm. IBA able to rose up part of sprout and length of roots, NAA able to rose up part of roots.Â Â